2014
DOI: 10.1073/pnas.1410024111
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction does not elicit a robust extension of replicative lifespan inSaccharomyces cerevisiae

Abstract: Calorie restriction (CR) is often described as the most robust manner to extend lifespan in a large variety of organisms. Hence, considerable research effort is directed toward understanding the mechanisms underlying CR, especially in the yeast Saccharomyces cerevisiae. However, the effect of CR on lifespan has never been systematically reviewed in this organism. Here, we performed a meta-analysis of replicative lifespan (RLS) data published in more than 40 different papers. Our analysis revealed that there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
5
45
0
2
Order By: Relevance
“…Recently, Huberts et al (33) reported that CR-induced lifespan extension could not be detected with their microfluidic dissection platform. In contrast, we observed a robust CR longevity effect with the HYAA-Chip that is consistent with results obtained from the conventional microdissection-based lifespan assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Huberts et al (33) reported that CR-induced lifespan extension could not be detected with their microfluidic dissection platform. In contrast, we observed a robust CR longevity effect with the HYAA-Chip that is consistent with results obtained from the conventional microdissection-based lifespan assay.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this discrepancy is the very low retention rate of the cells in Huberts' device. As noted in their paper (33), 85% of all cells were lost before reaching the end of the lifespan, and in their analysis, experimental data obtained from cells that were washed out before death were incorporated into the lifespan curve as rightcensored data using the Kaplan-Meier analysis. Notably, due to the very low retention rate of their platform, the contribution of the washed out cells to the resultant data were significantly larger than that of the retained cells that were tracked throughout their entire lifespan.…”
Section: Resultsmentioning
confidence: 99%
“…2014 [21] was downloaded and lifespan data from BY4741 cells grown using the microfluidic platform in 2% glucose was used to evaluate lifespan curves generated with and without censored data.…”
Section: Methodsmentioning
confidence: 99%
“…The role of cell size is controversial. Cell size has both been suggested to be independent from replicative lifespan [1317], and causal to it [18–20] and has also previously been studies in microfluidic devices [912,2123]. Ribosomes, which are involved in cell size control [14], have been robustly shown to extend lifespan when knocked out in yeast and higher organisms [2430], and have also been causally implicated in aging [31].…”
Section: Introductionmentioning
confidence: 99%
“…In one case, Huberts et al reported that the longevity-promoting effect of caloric restriction is not seen in their microfluidic design. Their observations were accompanied by an interesting meta-analysis showing that studies showing the protective effects of dietary restriction in yeast generally reported control populations that were shorter-lived than the norm 52 . Later, Jo et al found that dietary restriction does increase longevity in cells aged in their device, noting that the conclusions of Huberts et al .…”
Section: Considerationsmentioning
confidence: 99%